Waardenburg Syndrome - Muhammad Raheel Zafar, Asma Parveen, Zara Shahbaz, Rai Muhammad Asghar , Shaukat Hussain, Muhammad Tayyab (Journal of Rawalpindi Medical College, 2018)
Waardenburg syndrome is a rare genetic disorder with at least 1,400 cases has been reported in medical lecture.In waardenburg syndrome a patient presents with hypopigmented areas of skin,white forelock of hairs,difference in the colour of both iris and some associated conditions like hirschsprung disease,malformation of upper limbs as well as certain abnormalities of CNS. 1 It may be evident at birth (congenital).Primary features often include distinctive facial abnormalities diminished pigmentation of the hair, the skin, and/or the iris of both eyes (irides); and/or congenital deafness. In addition, pigmentary abnormalities may include a white lock of hair growing above the forehead (white forelock); premature graying or whitening of the hair; differences in the coloration of the two irides or in different regions of the same iris (heterochromia irides); and/or patchy, abnormally light (depigmented) regions of skin (leukoderma). Some affected individuals may also have hearing impairment due to abnormalities of the inner ear (sensorineural deafness). 2-4